Assessment of Nursing Students’ Knowledge about Gastritis - Shraida, Amjed Abdulabbas; Kareem, Maryam Mohammed Ali; Al-Abedi, Haider Mohammed Haloob (Central Asian Journal of Medical and Natural Science, 2025)
Gastritis is a prevalent gastrointestinal condition with significant health implications, affecting individuals worldwide due to factors such as lifestyle habits, stress, dietary patterns, and infections like *Helicobacter pylori*. Nursing students, who often face academic pressures and irregular eating habits, may be particularly susceptible to this condition. This study aimed to assess nursing students' knowledge about gastritis and explore the relationship between their demographic characteristics and knowledge levels. A cross-sectional descriptive study was conducted at the College of Nursing, University of Kufa, Iraq, from October 2024 to February 2025. A convenience sample of 60 second-, third-, and fourth-year nursing students participated. Data were collected using a structured questionnaire covering demographic information and 20 items assessing knowledge of gastritis, including its etiology, symptoms, pathophysiology, classification, risk factors, and complications. Statistical analysis was performed using SPSS version 25, employing descriptive and inferential statistics (Chi-square test). The results revealed that the majority of participants were aged 18– 24 years (96.7%), female (63.3%), and urban residents (61.7%). The overall knowledge score was moderate (mean = 1.43), with significant variations across academic years. Fourth-year students demonstrated higher knowledge levels compared to their peers. Key gaps were identified in areas such as diagnostic tests, complications, and nursing care plans. A significant association (p ≤ 0.05) was found between knowledge levels and demographic factors like academic year and residency. The study concludes that while nursing students possess foundational knowledge about gastritis, critical gaps remain. Recommendations include enhancing the nursing curriculum with detailed gastrointestinal content, conducting targeted workshops, and promoting healthy lifestyle practices. Further research with larger and more diverse samples is encouraged to validate these findings and develop effective educational interventions.